Successful Administration of the Influenza Vaccine after Prior Serum Sickness in an HIV-Positive Patient - Kammeyer, Joel (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.